If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5y-11=-8(y+3)
We move all terms to the left:
5y-11-(-8(y+3))=0
We calculate terms in parentheses: -(-8(y+3)), so:We get rid of parentheses
-8(y+3)
We multiply parentheses
-8y-24
Back to the equation:
-(-8y-24)
5y+8y+24-11=0
We add all the numbers together, and all the variables
13y+13=0
We move all terms containing y to the left, all other terms to the right
13y=-13
y=-13/13
y=-1
| 3(w-1)=-6w+6 | | 7x=2(x-4 | | -2w+12=-6(w+2) | | x²-3x-130=0 | | x-5/4x-2x+6/16x=x-1/12x | | .0333x+2=-1 | | 226-4x=180 | | (x^2-16^2)=16x+1 | | 180-4x+46=180 | | 6(7)^x=2058 | | 3.7q-5.4-4.1q=-1.4q-1.7 | | 14-2(x+6)=-14 | | 32-18x-x^2=0 | | 2x-10+4x=20 | | -3(-2x-25)=105 | | k/5.2+91.9=47.2 | | -7(n+3)+23=-5n-8 | | -5y+8=6y+5 | | -29=-43-(-2)x | | -4/9*x=16/27 | | Y=-3/2x+19/2 | | 2x+4x.X=10 | | 62=14x-8 | | -6/7x+17=-25 | | 4-10=3z | | x+(x*0.2)=17000 | | -6-11=8x+15-7x | | 30=9+6x | | w*5=10 | | w*5=1 | | 2x2+13x-6=1 | | 12m+4=8m-30 |